2016
DOI: 10.1002/cbm.2016
|View full text |Cite
|
Sign up to set email alerts
|

Dating violence and physical health: A longitudinal lens on the significance of relationship dynamics and anti‐social lifestyle characteristics

Abstract: Findings suggest the need to further examine the physical health consequences of dating violence, with a particular focus on the relationship context and other potential confounding forces. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Although these prevalence rates vary according to the questionnaires used, the types of dating violence examined and the duration of romantic relationships reported show that a significant number of adolescents and young adults can experience dating violence, which have the potential to generate negative consequences in their physical and mental health (Wincentak et al, 2017). Among the physical and mental health difficulties associated with dating violence victimization are depression, anxiety, low self-esteem, alcohol and drug use, unhealthy weigth control behaviors, suicidal ideation, sexual risk behaviors and academic problems (Copp, Giordano, Longmore & Manning, 2016;Foshee, McNaughton, Gottfredson, Chang & Ennett, 2013;Lormand et al, 2013;Ludin et al, 2018;Parker, Johnson, Debnam, Milam & Bradshaw, 2017;Peterson et al, 2018;Rubio-Garay, Carrasco, Amor & López-González, 2015). Hébert, Lavoie, Vitaro, McDuff and Tremblay (2008), found that the risk of presenting an internalizing disorder was 10 times higher, among 774 Canadian teenagers who had a history of victimization of child sexual abuse and dating violence, being seven times higher in the case of externalizing disorders.…”
mentioning
confidence: 99%
“…Although these prevalence rates vary according to the questionnaires used, the types of dating violence examined and the duration of romantic relationships reported show that a significant number of adolescents and young adults can experience dating violence, which have the potential to generate negative consequences in their physical and mental health (Wincentak et al, 2017). Among the physical and mental health difficulties associated with dating violence victimization are depression, anxiety, low self-esteem, alcohol and drug use, unhealthy weigth control behaviors, suicidal ideation, sexual risk behaviors and academic problems (Copp, Giordano, Longmore & Manning, 2016;Foshee, McNaughton, Gottfredson, Chang & Ennett, 2013;Lormand et al, 2013;Ludin et al, 2018;Parker, Johnson, Debnam, Milam & Bradshaw, 2017;Peterson et al, 2018;Rubio-Garay, Carrasco, Amor & López-González, 2015). Hébert, Lavoie, Vitaro, McDuff and Tremblay (2008), found that the risk of presenting an internalizing disorder was 10 times higher, among 774 Canadian teenagers who had a history of victimization of child sexual abuse and dating violence, being seven times higher in the case of externalizing disorders.…”
mentioning
confidence: 99%
“…While dating and sexuality should be normal, expected and positive aspects of adolescent development (Collins, 2003;Meier & Allen, 2009;Tolman & McClelland, 2011), there is evidence that men's violence against young women is prevalent in Australia (Australian Bureau of Statistics, 2016). Dating violence is known to have several significant short and long term mental, physical and reproductive health impacts as well as social and behavioural impacts on young women (Bonomi, Anderson, Nemeth, Rivara, & Buettner, 2013;Copp, Giordano, Longmore, & Manning, 2016;Nahapetyan, Orpinas, Song, & Holland, 2014). There is also an economic burden associated with men's violence against women, which includes dating violence, and conservative estimates show that gendered IPV cost the Australian economy about $22 billion for the year -16 (KPMG Australia, 2016.…”
Section: Rationalementioning
confidence: 99%
“…Indeed, examination of longitudinal patterns reveals that rates of partner violence increase across the adolescent period, reaching a peak during young adulthood (i.e., between the ages of 17–20 for male youth and 21–24 for female youth) (Johnson, Giordano, Manning, & Longmore, ). Furthermore, the experience of relationship violence in adolescence has consequences for psychosocial development, as well as mental and physical health outcomes (e.g., Ackard, Eisenberg, & Neumark‐Sztainer, ; Copp, Giordano, Longmore, & Manning, ,b; Exner‐Cortens, Eckenrode, & Rothman, ; Haynie et al., ). Preliminary research on youth dating violence has helped to identify risk factors (e.g., Foshee et al., ; Giordano, Soto, Manning, & Longmore, ; O'Keefe, ; Vagi et al., ), and has guided the development of intervention and prevention programming (Coker, Banyard, & Recktenwald, ; Cornelius & Resseguie, ; Taylor, Stein, Mumford, & Woods, ).…”
Section: Economic Considerations Relationship Conflict and Ipv/aramentioning
confidence: 99%
“…Furthermore, research adopting a social learning approach to partner violence is often somewhat unsophisticated, as scholars tend to focus on the direct transmission of certain behaviors (i.e., imitation). Yet there is more to social learning than imitation; individuals observe and may internalize complex scripts for violent behavior, verbal tactics and styles of communication, and attitudes accepting of violence (Copp, Giordano, Longmore, & Manning, ,b). Consistent with prior research, we include in our models indicators of violence in the family of origin.…”
Section: Economic Considerations Relationship Conflict and Ipv/aramentioning
confidence: 99%